REALISASI CCTV CERDAS BERBASIS MIKROKONTROLER DAN REAL TIME 3D FACE RECOGNITION - Arkhiansyah, Yuni; Setiawan, Dodi Yudo (Jurnal Informatika, 2015)
CCTV which available now is not provided with the ability to recognize but only to record and must be observed directly by users. This way will heighten the level of human error, therefore this paper will build 3D face recognition to be implemented on CCTV provided with camera control using microcontroller. Microcontroller will assist in the process of face recognition. The 3D face recognition is selected in the process of face recognition because it has some benefits that namely not dependent to the lighting.Â Key words: CCTV, 3D face recognition, microcontroller